Grau de expressão da sirtuína-1 (SIRT-1) em tecido tumoral de mulheres com câncer de mama : valor prognóstico independente ou associado a variáveis clínicas, histopatológicas e imuno-histoquímicas - Sartori, Juliano (2016)
Despite the advances resulting from the molecular characterization of breast cancer that allowed the use of more selective therapeutic targets, the disease still causes different clinical outcomes with high rates of recurrence and mortality. In this context of complexity and heterogeneity of breast cancer, are important the investigations of new biomolecular markers related to breast oncogenesis that may contribute to know the prognosis and improve the clinical management of patients. The sirtuin-1 (SIRT-1) is a histone deacetylase implicated in various epigenetic critical functions into cells, among these, the maintenance of genomic stability, proliferation and cell aging. The aim of this study was to investigate the grade of expression of the sirtuin- 1 (SIRT-1) in a cohort of 457 women with breast cancer and verify the effect, independent or in combination with other variables in the prognosis of these patients. It is a survival analysis study based on hospital medical records of women with breast cancer undergoing treatment in Erechim-RS from 2003 to 2013 and followed until 31 July 2015. The analysis of the grade of SIRT-1 expression was performed by immunohistochemistry in 123 patients (26.9%) of the total cohort. Overall survival specific disease (OS) was estimated by the Kaplan-Meier method and the risk of death from breast cancer by the method of Cox proportional hazards. The research was approved by the Research Ethics Committee of PUC-RS as reported number 465.362. The median age was 57.4 years and the median estimate of breast cancer survival was 79.6% at 5 years and 69.1% at 10 years, with median follow-up time of 61.9 months. Risk factors associated with worse prognosis were: age between 60 and 69 years (HR = 1.88; 95% CI 1.02 - 3.44; p = 0.042); older than 70 years (HR = 2.92; CI 95% 1.70 - 5.01; p = 0.000); tumor size greater than 2 cm (HR = 1.86; CI 95% 1.04 -3.36; p = 0.038); metastasis in 4 or more axillary lymph nodes (HR = 2.37; CI 95% 1.38 - 4.08; p = 0.002); located clinical staging (CS II, TNM) (HR = 3.39; CI 95% 1.35 - 8.51; p = 0.009); advanced clinical staging (CS III, TNM) (HR = 6.32; CI 95% 2.49-16.08; p = 0.000); high histologic grade (HR = 6.32; CI 95% 1.63 - 29.99; p = 0.008); triple negative molecular profile (HR = 2.33; CI 95% 1.19 - 4.58; p = 0.014) and radical surgery (HR = 2.10; CI 95% 1.31 - 3.36; p = 0.002). The positive expression of progesterone receptor (HR = 0.52, CI 95% 0.34 - 0.79; p = 0.002) was a better prognostic factor for patients. The grade of overexpression of SIRT-1, defined as nuclear expression of SIRT-1 greater than 80% was observed in 6.5% of cases. The SIRT-1 overexpression characterized a subgroup of women who had a worse prognosis with shorter survival and increased risk of death from breast cancer (HR = 2.66; CI 95% 1.03 - 6.86; p = 0.043). Multivariate regressive models (Cox) were constructed and the overexpression of SIRT-1 remained significant statistic demonstrating independent factor associated with worse prognostic in breast cancer. Therefore, the evaluation of the grade of expression of the SIRT-1, in the cohort of Erechim-RS, proved to be an independent prognostic marker for analysis of the risk of death from breast cancer.